Educational requirements to confront the methods of intellectual extremism among Baghdad University students from the viewpoint of their teachers - Ali, Ahmed Hussein; Mohammed Khalaf, Hisham (Al-Adab Journal, 2020)
Intellectual extremism has become a global phenomenon that all Arab and Western societies suffer from, as many educated and illiterate young people have slipped into it. Intellectual extremism has become a dangerous and rapidly spreading disease among university students. Perhaps the reason behind this is knowledge openness, technological progress, globalization, intellectual conflict and misunderstanding Or weakness of the truth of religion and legal constants, and this has pushed all educational, educational and social institutions in order to confront the methods of intellectual extremism seeking to advance and preserve students, as universities bear the great responsibility in that as Thought institutions and research centers from research and community role as well as the educational role, and seeks a researcher to highlight the importance of the role of the requirements of educational social, cultural, political, economic, religious and sports to counter intellectual extremism and methods of prevention of them that have become threatening the security and stability of society. The researcher has built and developed the research tool, which is a questionnaire that includes (60) items distributed over six different fields that contain educational requirements to confront the methods of intellectual extremism. The research sample was chosen by the random layer method, which numbered (400) professors and professors at (188) of males and (212) of females distributed over three different colleges who were chosen by drawing method from the total research community of (6321) professors and professors.